Análise do fatores para o compartilhamento do conhecimento operário em indústrias do setor automotivo no Brasil - Petrini, Stefano [UNESP] (2016)
Recent research about the identification of factors that contribute to better sharing of knowledge and ways to evaluate this topic highlight the importance of knowledge management for the organization. Exploring opportunities in this scenario, the present study examines the share of the workers' knowledge in the automotive industry by factors related to the Production Organization, Work Organization and Knowledge Management, with attention to the influence of organizational and interpersonal context in the knowledge sharing process. This delimitation of the industrial sector in the light of the production area is justified by this area has dependence of the workers' tacit knowledge. The research uses a qualitative and quantitative approach in survey format and uses a questionnaire with managers (coordinators and supervisors) to assess the importance of leveraging factors of knowledge management in the view of the leadership body. It employed the Incomplete Pairwise Comparison method proposed by Harker (1986) based on the Analytic Hierarchy Process of Saaty (1977). The survey shows an integration between the factors and highlights the importance of systemic and technical conversation among the workers to improve their knowledge sharing, plus the role of communication, training and work instruction in the knowledge conversion processes. This research expands the theme of the conceptual limits knowledge management found in literature and contributes mainly in managerial direction for the qualification and learning new employees in the continuous process of recycling knowledge and mitigation of knowledge waste. Thus, it contributes to the promotion of an enabling environment for the creation and sharing of knowledge by the people of the workers' environment.